2007
DOI: 10.1264/jsme2.22.145
|View full text |Cite
|
Sign up to set email alerts
|

2,4-Dichrolophenoxyacetic Acid-degrading Genes from Bacteria Isolated from Soil in Japan: Spread of Burkholderia cepacia RASC-type Degrading Genes Harbored on Large Plasmids

Abstract: Fourteen strains of 2,4-dichrolophenoxyacetic acid (2,4-D)-degrading bacteria were isolated from soil samples from eight different sites in Japan and identified as members of the genera Burkholderia, Cupriavidus, and Sphingobium. To characterize them in view of the 2,4-D-degrading genes that they had, the strains were divided into three groups based on similarities of PCR-amplified partial nucleotide sequences of their 2,4-D-degrading genes to the sequences of well-characterized 2,4-D-degrading genes, tfdA, tf… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
15
0

Year Published

2008
2008
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 14 publications
(15 citation statements)
references
References 54 publications
0
15
0
Order By: Relevance
“…2). The organization of the tfd gene cluster in strain RASC, in which the partial nucleotide sequences of tfdA, tfdB and tfdC have ¢98 % similarity to those of pM7012 (Sakai et al, 2007), has not been reported. The second tfd gene cluster, tfdC II E II B II in pM7012, was not a simple duplication of part of the first gene cluster, tfdB I E I C I D I R I .…”
Section: 4-d Degradation Genesmentioning
confidence: 99%
See 1 more Smart Citation
“…2). The organization of the tfd gene cluster in strain RASC, in which the partial nucleotide sequences of tfdA, tfdB and tfdC have ¢98 % similarity to those of pM7012 (Sakai et al, 2007), has not been reported. The second tfd gene cluster, tfdC II E II B II in pM7012, was not a simple duplication of part of the first gene cluster, tfdB I E I C I D I R I .…”
Section: 4-d Degradation Genesmentioning
confidence: 99%
“…strain NK8 (Francisco et al, 2001) and C. necator strain NH9 (Ogawa & Miyashita, 1995) as recipients, and strains M701 and other strains with pM7012-like plasmids obtained in the previous work (Sakai et al, 2007) as donors. However, no transconjugant was detected in this experimental system.…”
Section: Spread Of 24-d Degradation Megaplasmids Related To Pm7012mentioning
confidence: 99%
“…However, there is growing concern over the increased use of such pesticides 29) , as well as over the microbial community that degrades and thus detoxifies penticides 11,33) . The fumigation of soil suppresses not only target plant-parasitic nematodes but also non-target free-living nematodes and microbes.…”
mentioning
confidence: 99%
“…They also characterized a 2,4-D-and 2,4,5-T-degrading enrichment culture by 16S rRNA and benA gene-targeted PCR-DGGE, and suggested the major role of Burkholderia species in degrading these chemicals (51). Sakai et al (138) reported that the Burkholderia cepacia RASC type 2,4-D-degrading genes harbored on large plasmids spread out among 2,4-D-degrading bacteria isolated from soil in Japan. A soil bacterial community capable of degrading 3-chlorobenzoate was characterized by 16S rRNA and benA gene-targeted PCR-DGGE (112,113).…”
Section: Biodegradation Of Hazardous Chemicals: One Of the Fastest Grmentioning
confidence: 99%